Gut microbiome modifications over time when removing in-feed antibiotics from the prophylaxis of post-weaning diarrhea in piglets - Paola Cremonesi; Filippo Biscarini; Bianca Castiglioni; Carlo Angelo Sgoifo; R. Compiani; P. Moroni (2022)
Post-weaning diarrhea (PWD) in pigs has mainly an infectious basis and control strategies are centred on antibiotics added to the diet. Given concerns on the spread of multi-resistant bacteria, it is necessary to develop alternative prophylactic approaches to control PWD in piglets. The most promising alternative strategies are based on substances that act indirectly on the bacteria by stimulating the immune system or by improving gut health. The aim of this study was to evaluate the effect on the gut microbiota of feed supplemented with a mixture of essential oils (garlic and oregano) in weaning piglets, compared to traditional PWD management (in-feed antibiotics) and to a control group without any diet supplementation. The study involved 197 piglets from 18 litters in a single farm. The piglets were followed from birth to day 58 of age and were weaned at day 26. During the experimental period, the animals were monitored for weight and growth, average daily gain, morbidity and mortality. For the metataxonomics analysis, rectal samples were collected from 17 piglets from the three experimental groups at 4 different time-points (days 1, 12, 26 and 58). Results revealed that the gut microbiota in pre- and post-weaning piglets was dominated by the phyla Firmicutes (51%), Bacteroidetes (25%) and Proteobacteria (16%), which together make up for over 90% of the entire piglet core gut microbiota. The core microbiota comprised 10 taxa before weaning and 43 taxa after weaning, with 7 taxa overlapping between timepoints: two of them (Prevotella 9, p-value = 0.00095; Solobacterium p-value = 0.00821) were significantly more abundant after weaning. All alpha diversity indexes were significantly different between pre- and post-weaning, while only Shannon and Simpson diversity and equitability were significantly different between treatments. Based on the matrix of Bray-Curtis dissimilarities, samples showed clear clustering per timepoint (before and after weaning, p-value < 0.001) and between treatments by timepoint (p-value = 0.0086). The oil-diet group showed a consistently higher F:B ratio at all timepoints. These results show that the pig gut microbiota changes significantly with weaning, and suggest that the use of essential oils as feed supplementation to control PWD does not seem to alter sgnificantly the microbiota nor the growth parameters of piglets, however modifications of specific taxa may occur.